PERAN MEDIA VISUAL GAMBAR DALAM PEMBELAJARAN MENGARTIKULASIKAN SECARA TERTULIS TEKS ARGUMENTASI PADA SISWA KELAS XI SMAN 4 KOTA KEDIRI TAHUN PELAJARAN 2025/2026 - Intan Nuraina Sari; Moch. Muarifin; Andri Pitoyo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study critically investigates the “role of visual image media in the teaching and learning of argumentative writing skills among eleventh-grade students of SMAN 4 Kediri in the 2025/2026 academic year.” The research is grounded in the observed deficiency in students’ abilities to “generate ideas, construct coherent and logical arguments, and systematically organize argumentative texts.” A quantitative research approach was employed using a quasi-experimental design, specifically a posttest-only control group model. The participants comprised two groups, namely an experimental class consisting of 30 students and a control class consisting of 26 students. Data were collected through writing assessment tests and subsequently analyzed using descriptive statistics and inferential statistics through an Independent Sample T-test. The results demonstrate a significant disparity between the two groups. The experimental class attained a mean score of 92.83, whereas the control class achieved a mean score of 75.00. “The statistical analysis yielded a t-value of 8.113 with a significance level of 0.000 (< 0.05), thereby indicating that the null hypothesis was rejected and the alternative hypothesis was accepted” (Sugiyono, 2022). These findings substantiate that visual image media exerts a significant positive effect on students’ argumentative writing competence. The presence of visual stimuli does not merely function as an auxiliary instructional tool, but rather serves as a “cognitive bridge connecting observation, imagination, and critical reasoning,” thereby enabling students to articulate ideas in a more logical, coherent, and meaningful written form.